Experimental Study of Pre-mixed Flames on a Multi-Hole Matrix Burner - Raghavan, Vasudevan (International Journal of Integrated Engineering, 2012)
This paper deals with an experimental investigation of the flame characteristics of premixed Liquefied Petroleum Gas (LPG) - air mixtures with different equivalence ratios on a multi-hole matrix burner. Lowest possible fuel-lean mixing conditions are envisaged. Results show that the flame pattern changes into four different types which are oscillatory flames in the middle region, flames with oscillations along the centerline, flames with very little oscillations and stable flames from all the holes. Species concentration measurements are performed with the help of  gas analyzer and the results show that the concentrations of carbon-monoxide and oxygen decreases, whereas that of carbon-dioxide and nitric oxide increases with increase in the volumetric flow rate of LPG and air mixture. In addition to this, temperature measurements are carried out using a K-type thermocouple over the burner surface at different heights. Temperature contours for each plane have been presented.